Isolating Reactions at the Picoliter Scale: Parallel Control of Reaction Kinetics at the Liquid-Liquid Interface - Phan-Quang, Gia Chuong (2017)
Miniaturized liquid–liquid interfacial reactors offer enhanced surface area and rapid confinement of compounds of opposite solubility, yet they are unable to provide in situ reaction monitoring at a molecular level at the interface. A picoreactor operative at the liquid–liquid interface is described, comprising plasmonic colloidosomes containing Ag octahedra strategically assembled at the water-in-decane emulsion interface. The plasmonic colloidosomes isolate ultrasmall amounts of solutions (<200 pL), allowing parallel monitoring of multiple reactions simultaneously. Using the surface-enhanced Raman spectroscopy (SERS) technique, in situ monitoring of the interfacial protonation of dimethyl yellow (p-dimethylaminoazobenzene (DY)) is performed, revealing an apparent rate constant of 0.09 min−1 for the first-order reaction. The presence of isomeric products with similar physical properties is resolved, which would otherwise be indiscernible by other analytical methods.